Technique for Ensuring Type I Bubble Formation for Pre-Descemet Endothelial Keratoplasty Preparation. Issue 10 (October 2019) - Saint-Jean, Alejandro; Soper, Mark; Den Beste, Kyle; Iverson, Shawn; Price, Marianne O.; Price, Francis W.
Abstract : Purpose: To describe a technique that ensures the production of a type 1 bubble when preparing pre-Descemet endothelial keratoplasty (PDEK) grafts with a high rate of predictability. Methods: Donor corneas were placed on a support disc, and a blunt instrument was used to score 360 degrees of the peripheral Descemet membrane and endothelium just inside the trabecular meshwork. Air was injected in several short bursts and several stages with a 30-gauge needle on a 3-mL syringe 2.0 mm away from the limbus to create a type 1 big bubble. The technique was tested by 2 operators (M.S. and A.S.-J.) in 26 human donor corneas, including 12 for possible transplantation, over a 9-month period. Anterior segment optical coherence tomograph (AS-OCT) was performed in 1 case proving a type 1 bubble. Results: A type 1 big bubble was successfully created in 24 of 26 attempted cases (92.3%). The technique was used successfully to obtain PDEK tissue for transplant in 9 eyes. One case was not technically acceptable because of diffuse cell loss (>10%); however, the bubble preparation itself was successful. One case had a mixed bubble because of incomplete scoring, resulting in a Descemet membrane endothelial keratoplasty graft used for transplant. One case failed to form any bubble likely because the scoring was too central. Of a total of 26 cases, 14 cases were for practice. Conclusions: The Soper technique significantly improved the success rate of creating a type 1 bubble for PDEK preparation. Abstract : Supplemental Digital Content is Available in the Text.